2012
DOI: 10.1513/pats.201201-010aw
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells and Pulmonary Fibrosis: Cause or Cure?

Abstract: Pulmonary fibrosis is a feature of a number of important lung diseases, and alveolar epithelial injury plays a key role in their pathogenesis. Traditionally, type II alveolar epithelial cells have been viewed as the progenitor cells of the alveolar epithelium; however, recent studies have identified a number of other progenitor and stem cell populations that may participate in alveolar epithelial repair. These studies suggest that the injury microenvironment plays a role in regulation of progenitor cell popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 97 publications
1
24
0
Order By: Relevance
“…However, there is a lack of preclinical and clinical studies of stem cell therapy for radiation-induced adverse effects in the lung, particularly in radiation-induced fibrosis (54,75). There are also only few ongoing clinical trials with mesenchymal stem cells (MSCs), also referred to as multipotent mesenchymal stromal cells (MPSCs) in chronic lung disease, including their therapeutic application in patients with idiopathic pulmonary fibrosis (77).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of preclinical and clinical studies of stem cell therapy for radiation-induced adverse effects in the lung, particularly in radiation-induced fibrosis (54,75). There are also only few ongoing clinical trials with mesenchymal stem cells (MSCs), also referred to as multipotent mesenchymal stromal cells (MPSCs) in chronic lung disease, including their therapeutic application in patients with idiopathic pulmonary fibrosis (77).…”
Section: Introductionmentioning
confidence: 99%
“…5,12 In fact, MSCs have been approved for use in clinical trials in patients with IPF. 8 In studies showing beneficial effects of MSCs in the BLM model, however, lung fibrotic injury was significantly reduced by delivery of MSCs during not the fibrotic phase but the early inflammatory phase. 5 Similarly, it has been demonstrated that bone marrow mesenchymal stromal cells systemically injected into mice during the fibrotic phase of radiation-induced lung injury mostly acquire a fibroblast phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research has identified three related but distinct biological roles for TREM-2: as a phagocytic and immune modulatory receptor on macrophages, as a neuroprotective factor expressed on microglia (reviewed in Reference 5), and as a regulator of osteoclast differentiation (6). Myeloid cell TREM-2 has been found to be induced during inflammation (7), to secrete antiinflammatory cytokines and tame TLR signaling (8)(9)(10), and to act as a direct phagocytic receptor for bacteria (11). Thus, TREM-2 may also have a role to play in sepsis.…”
Section: Triggering Receptor Expressed On Myeloid Cells-2: a New Allymentioning
confidence: 99%
“…With respect to MSC effects on lung fibrosis, a systematic review of the English language literature identifies 12 published manuscripts that have investigated the effects of syngeneic, allogeneic, or xenogeneic MSC administration in mouse, rat, or pig models of bleomycininduced lung fibrosis, the most commonly used preclinical model (8,9). Notably, MSC administration by either systemic or intratracheal route during the early stage of the injury ameliorates acute inflammation and is protective against subsequent development of fibrotic changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation